Emotional education in legislation: Analysis based in minimum contents decrees from LOMLOE - Lozano, María Yazmina; Hernández Arroyo, Sara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Emotional education as a topic for investigation has a long tradition, with different authors both international and national. These studies maintain that comprehensive education for students require the inclusion of aspects both cognitive and abilities connected with self -control, self-knowledge, or collaboration between partners, among other things. Next lines, royal decrees of minimum contents based in LOMLOE are going to be analysed to verify if it is included and how it has been done.